Retinal Detachment Surgery in Oculocutaneous Albinos Patient - Syed Fawad Rizvi, Washoo Mal, Shakir Zafar, Shahab ul Hasan Siddiqi (Pakistan Journal of Ophthalmology, 2013)
This is an interventional case report of a 30 years old male patient of oculocutaneous albinism with high myopia associated with retinal detachment in both eyes. He had best corrected visual acuity of hand movement in right eye due to fresh rhegmatogenous retinal detachment and perception of light in fellow eye because of long standing retinal detachment. Micro incision vitrectomy surgery was done in right eye after flattening of retina with PFCL, endolaser photocoagulation attempted but failed to get adequate burns over tear and detached retina. Then cryopexy was performed around the retinal tear and 360° of peripheral retina.